Quantitative metabolomics approach reveals dynamics of primary metabolites in 'Kinnow' mandarin (C. nobilis × C. deliciosa) during advanced stages of fruit maturation under contrasting growing climates. Issue 1 (2nd January 2020) - Saini, Manpreet Kaur; Capalash, Neena; Varghese, Eldho; Kaur, Charanjit; Singh, Sukhvinder Pal
ABSTRACT: This study employs a quantitative metabolomics approach to study the dynamics of primary metabolites in 'Kinnow' mandarin as influenced by maturation and ripening under contrasting growing climates. Fruit samples were harvested at regular intervals during the advanced stages of maturation and ripening from two contrasting growing locations, one under subtropical–arid (STA) climate and the other under subtropical–humid (STH) climate. Fruit juice samples were analysed using a targeted liquid chromatography-mass spectrometry (LC/MS) technique for identification and quantitation of primary metabolites such as sugars, organic acids and some vitamins. Significant ( p < 0.05) differences in the metabolite concentrations were observed to be influenced by maturation stage and growing location. An increase in the concentration of sugars and B-complex vitamins was observed during the final stages of maturation approaching commercial maturity, whereas organic acids and vitamin C concentrations decreased. Fruit grown under STA climate exhibited a higher concentration of vitamin C and a lower concentration of organic acids than those grown under STH climate. The results suggest that fruit metabolism during the final stages of maturation and ripening under arid versus humid climatic conditions is a key determinant of the flavour and nutritional quality of 'Kinnow' mandarin.